The influence of human resource management practices and proactive personality on job performance among commercial bank employees - Hema, Subramaniam (2015)
This study examined the influence of three dimensions of human resource management practices which are compensation and benefits, training and development and performance appraisal and achievement together with proactive personality on job performance among the commercial bank employees in Kuala Lumpur, Malaysia. Job performance was measured by combining task performance and organizational citizenship behavior. The researcher’s intention of merging dimensions of human resource management practices and proactive personality on job performance is to validate the Determinants of Job Performance Model by Cardy and Dobbins and Waldman (1994). A total of 120 commercial bank employees participated in this study. Regression analysis was performed to test the research hypotheses. The results of this findings revealed that the two dimensions of human resource management practices (i.e. training and performance management and internal and external equity) did not have a significant influence on job performance. However, compensation and benefits were found to have impacted job performance significantly. Similarly, proactive personality was found to have significant influence on job performance. This study provided theoretical and practical implications